Humility and Influence: Female Agency and the Confraternity of Saint Rosalia in Eighteenth-Century Cuenca - Oleas-Mogollón, Isabel (Religion and the arts, 2021)
Abstract In June 1773 Doña Luisa García de Medina filed a lawsuit against the Spanish colonial government demanding the return of her generous donation to the confraternity of Saint Rosalia in Cuenca (Audiencia of Quito). This dispute provides a clear testimony of the influence of religious devotion and the power of female self-fashioning and agency. Doña Luisa’s piety, her promotion of the cult of Saint Rosalia, and her substantial donation allowed her to establish associations with leading local institutions and shape Cuenca’s sacred landscape and its inhabitants’ religious experience. Doña Luisa’s control of the processional route also identified her oratory as a space for spiritual introspection, self-representation, and social exchange. This article illustrates the importance of humility in the advancement of female agency in the colonial period. This research also proves that the study of religious confraternities supports a more inclusive construction of Spanish American history and shows the impact of female patronage in the civic space.